Perceived Social Support in Hemodialysis Patients - F Rafii; M Rambod; F Hosseini (Tehran University of Medical Sciences, 2009)
Background & Aim: Physical and psychosocial problems along with the changes in life style, put hemodialysis patients under pressure. It seems that social support decreases psychological stresses and improves quality of life. This study aimed to describe hemodialysis patients;apos perceptions on their social supports and related factors. Methods & Materials: This descriptive-correlational study is a part of a larger study. All patients (n=202) referred to the hemodialysis units of Iran University of Medical Sciences were recruited to the study during a four-months period. Data were collected using "Personal Resources Questionnaire" (PRQ 85-PART 2) and analyzed using SPSS v.14. Results: Findings revealed that the most patients (64.9%) had perceived social support at high levels. There were significant relationships between social support with economic status, gender and marital status (P<0.05). Findings also indicated that the statements of "I enjoy doing little extra things that make another person;aposs life more pleasant" and, "I belong to a group in which I feel important" had the highest and lowest scores respectively. Conclusion: Regarding the variety of perceptions in hemodialysis patients on social support and its related factors, nurses can prevent social isolation of these patients through identification of high risk groups and can also reduce their stresses and help them to improve their quality of life by providing adequate supportive interventions.